Productivity and energetics of rice (Oryza sativa) based cropping systems in Indo-Gangetic plains - BANJARA, TEJ RAM; BOHRA, J S; SINGH, DEO NARAYAN; SINGH, TEJBAL (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted at the Agricultural Research Farm, Banaras Hindu University, Varanasi, Uttar Pradesh during 2016–17 and 2017–18 to study the productivity and energetics of rice (Oryza sativa L.)-based cropping systems under irrigated condition. The experiment was conducted in randomized block design with three replications. The treatment comprised ten rice-based cropping sequences. Results revealed that rice-potato-green gram recorded significantly high system rice equivalent yield over rest of the cropping sequences during both the years of study. Energy input was recorded highest in rice-potato-green gram followed by rice-potato-cowpea fodder, rice-mustard-sudan grass fodder, rice-wheat-cowpea fodder and lowest in rice-berseem-cowpea fodder sequence. Rice-mustard-sudan grass fodder sequence recorded significantly high energy output, net energy, energy outputinput ratio and energy intensity as compared to rest of the cropping sequences during both the years of investigation, whereas energy productivity was high in rice-cabbage-cowpea fodder sequence compared to other sequences during both the years of experimentation. However, specific energy was higher in rice-wheat-green gram sequence than rest of the cropping sequences except rice-wheat sequence during second year of investigation where it remained at par with rice-wheat-green gram sequence.